The role of sediment on the energy availability for fishes in the upper Paraná river floodplain - doi: 10.4025/actascibiolsci.v34i4.9335 - Gimenes, Michele de Faveri; Takeda, Alice Michiyo; Benedito, Evanilde (Acta Scientiarum. Biological Sciences, 2012)
This study aimed to identify potential sources of organic matter in sediment, using stable isotopes of carbon (delta13C) and nitrogen (delta15N). Sediment samples were gathered from the margin and in center of three subsystems: Ivinheima, Paraná and Baia, in August/2001. The samples were fractionated granulometrically and separated by size (< 200 µm; 70-200 µm; > 70 µm), prepared and sent to CENA / USP, for identifying the isotopes proportions. Significant differences were detected in the isotopic ratios of the sediment only between sampling stations. The Baía channel presented the lowest delta13C values, while the highest ones were recorded in Paraná river. At this last, delta15N values were negative (-14.41‰). We did not verify significant difference in isotopic composition between the particle sizes of sediment, and between the sampling points. The main sources of carbon for the sediment were C3 macrophytes, periphyton and particulate organic carbon (POC).